Luminescence Thermometry with Nanoparticles: A Review - Ljubica Đačanin Far; Miroslav D. Dramićanin (Nanomaterials, 2023)
Luminescence thermometry has emerged as a very versatile optical technique for remote temperature measurements, exhibiting a wide range of applicability spanning from cryogenic temperatures to 2000 K. This technology has found extensive utilization across many disciplines. In the last thirty years, there has been significant growth in the field of luminous thermometry. This growth has been accompanied by the development of temperature read-out procedures, the creation of luminescent materials for very sensitive temperature probes, and advancements in theoretical understanding. This review article primarily centers on luminescent nanoparticles employed in the field of luminescence thermometry. In this paper, we provide a comprehensive survey of the recent literature pertaining to the utilization of lanthanide and transition metal nanophosphors, semiconductor quantum dots, polymer nanoparticles, carbon dots, and nanodiamonds for luminescence thermometry. In addition, we engage in a discussion regarding the benefits and limitations of nanoparticles in comparison with conventional, microsized probes for their application in luminescent thermometry.